Measuring meaningful learning through the experience of chemistry education students' in the basics of analytical chemistry practicum - Melur Regista Cahyani; Erlina Erlina; Ira Lestari; Masriani Masriani; Maria Ulfah (Pascasarjana Universitas Negeri Medan, 2024)
Chemistry Education students often engage in laboratory practicums to develop scientific process skills and enhance the meaning of chemistry learning, as seen in the course basic analytical chemistry. Previous research indicates that the basics of analytical chemistry practicum frequently focus solely on confirming basic knowledge, thus only leading to an improvement in basic experimental skills. This study aims to measure the level of meaningful learning achieved through the experiences of chemistry education students in in the basics of analytical chemistry practicum as evidence to improve the practicum curriculum in order to create more meaningful learning. The research method involves both quantitative and qualitative descriptive approaches, with quantitative data collected using the Meaningful Learning in the Laboratory Instrument (MLLI), which has been modified to measure students' affective and cognitive experiences after learning in the chemistry laboratory. The study involved 60 third semester students who had completed the basics of analytical chemistry practicum course. The results indicate that all aspects were rated as good, with percentage scores of 67% for affective aspects, 74% for cognitive aspects, and 69% for affective-cognitive aspects, yielding an overall average percentage score of 70%. These findings suggest that chemistry education students have achieved significant meaningful learning through their experiences in the basics of analytical chemistry practicum.